कुमाउनी गाथा : राजुला मालूशाही - Pokhariya, Dev Singh (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2004)
The book narrates the bravary of Rajula Malushahi. It also describes the socio-cultural status of Kumaoni.
Kumaoni Gaatha : Rajula Malushahi
Keywords: कुमाउनी गाथा : राजुला मालूशाही; Kumaoni Gaatha : Rajula Malushahi; Folklore; Hindi; Hindi; Kumaoni